Impacts of Protected Areas on Land Degradation, Vegetation Cover and Biodiversity: A Case Study of Minglot Wildlife Park Khyber Pakhtunkhwa Pakistan - Qasim, Muhammad; Afghan, Afghan (Annals of Arid Zone, 2019)
In the current study impact of protected areas were studied on land degradation, vegetation cover and biodiversity by comparing area â€œInsideâ€ and â€œOutsideâ€ of Minglot Wildlife Park. Significant differences were found in soil fertility. Generally, all the soil parameters had more variation in their values inside protected area as compared to the unprotected area. Protected area was much greener while the unprotected area appeared to have a brownish color indicating less vegetation. Expert interviews and questionnaire survey revealed that the protected area had more animal and plant species inside its boundary, which were not recorded outside. Proper compensation to local communities and effective policies with adequate resource harvesting methods can help further in controlling deforestation that is intruding into protected areas also.Key words: Protected areas, land degradation, wildlife park, Manglot, Pakistan